AN IN-DEPTH ANALYSIS OF FEMALE REPRESENTATION IN CONTEMPORARY INDIAN WEB SERIES (CAHIERS MAGELLANES-NS, 2024)
The online streaming services are grabbing viewers' attention and making the registers ring like never before. They are squabbling over television's stagnated content and the blossoming chances for the advent of rich, high-quality material. As internet streaming services tend to restock the entertainment market, the overly dramatic television programming makes room for the new and relatable stories they provide. The Covid 19 reportedly destroyed practically every industry, but it also gave rise to Over The Top (O.T.T) platforms and saw an increase in subscriber numbers. Different online media platforms have emerged as a result of new media, providing viewers with both entertainment and information. Users now have simpler access to media materials when viewing them online thanks to new media applications. Due to the pandemic, viewers have started to use and choose online media more frequently, especially for videos that are related to entertainment. However, expansion of O.T.T platforms & web series is having a big impact on how its customers are amused by online media services. According to research, O.T.T platforms are particularly popular among young people due to their ease of access. People turned to web series as a way to escape the monotony of everyday life because they were trapped inside their houses and had no other methods of entertainment. Additionally, a series was created for the internet to challenge preconceived notions about women and alter how women are portrayed in popular culture. The purpose of the study's audience surveys and the researcher's goal is to analyse this updated representation. Understanding the variables influencing the success of O.T.T platforms and how viewers are responding to changing representations of women in mainstream media is made easier with the use of the poll's information. Understanding how Indian women are portrayed in internet series is the goal of this study.